The Socio-Economic Determinants of Crime in Pakistan: New Evidence on an Old Debate - Nabeela Khan; Junaid Ahmed; Muhammad Nawaz; Khalid Zaman (Arab Economic and Business Journal, 2015)
Crime appears to be strictly related to the level of education attained and to individuals' economic and social background. The objective of the study examines multiple factors i.e., education, unemployment, poverty and economic growth which contributed to the rate of crimes in Pakistan during the period of 1972-2011. The study finds a positive relationship between crime rates and unemployment rate in Pakistan. Higher unemployment diminishes the rate of return of legal activities, and is more likely to increase the return of illegal activities. There is a significant negative relationship between the crime rates and the higher education. More education directly induces high earnings of individuals and may increase both the opportunity cost of crimes and the cost of time spent in criminal activity. The study further assesses that GDP per capita leads to higher crime rates in the long-run but to lower rates in the short-run. Higher income shows that there are greater benefits for criminals as for thefts and robberies. Affluent areas attract more criminals due to the opportunities available to them. Finally, there is a positive relationship between the crime rates and poverty in the long-run but there is a negative relationship in the short-run. Poverty may lead to a high level of stress and mental illness which in turn causes individuals to adopt the criminal behavior. The study posits a caution that policy formulation in ameliorating crimes in Pakistan should anchor both social and economic factors.
Keywords: 330; Crime rates; Higher education; GDP per capita; Pakistan